Application of a modified MWCNT-based d-µSPE procedure for determination of bisphenols in soft drinks. (15th August 2022) - Sobhi, Hamid Reza; Mohammadzadeh, Farzaneh; Behbahani, Mohammad; Yeganeh, Mojtaba; Esrafili, Ali
Highlights: Dispersive µ-solid phase extraction. Carboxylated multi-walled carbon nanotubes modified with silver nanoparticles. Trace detection of two bisphenolic compounds at µg L −1 levels. Fast and efficient extraction of bisphenol A and bisphenol S. Sample pre-treatment of water and soft drink samples. Abstract: Herein, a facile dispersive micro-solid phase extraction (d-µSPE) procedure using carboxylated multi-walled carbon nanotubes modified with silver nanoparticles (Ag/MWCNTs-COOH) was successfully developed for the adsorption and subsequent determination of low levels of two well-known contaminants, namely bisphenol A and S (BPA and BPS) in water and soft drink samples. The detection and measurement of the above-mentioned compounds were performed by HPLC-UV instrument. The applied d-µSPE procedure has several advantages such as rapidity, high degree of sensitivity, precision and efficiency. A combination of polar/non-polar interactions seems to play a key role in the adsorption process. Under the optimized conditions, the calibration curves were linear over the concentration range of 1–500 µg/L for the both targets. The practical limit of quantifications (LOQ) for the both analytes were determined to be 1.0 µg/L. The average relative recoveries obtained from the fortified samples varied between 92 and 110% with the relative standard deviations (RSD%) of 2.9–9.5%.